2016
DOI: 10.7287/peerj.preprints.2101v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling potential distribution of Indo-Pacific humpback dolphins (Sousa chinensis) in the Beibu Gulf, China

Abstract: 14Background. Mapping key habitats of marine mega-vertebrates with high mobility is crucial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The dolphin distribution feature, similar to other cetaceans, mostly results from their foraging for prey (Davis et al 2002;Moura et al 2012;Thorne et al 2012). Studies of the humpback dolphin feeding habits demonstrated that above 20 kinds of demersal and shoaling fish found in productive estuaries were inclusive in their diet (Barros & Cockcroft 1991;Barros et al 2004;Jefferson & Karczmarski 2001;Pan et al 2013;Parra 2006;Parra & Jedensjö 2009;Ross et al 1994;Wang 1965;Wang 1995). That's why the humpback dolphins preferred to estuaries, for feeding on diverse and abundant fish.…”
Section: Habitat Preferencementioning
confidence: 99%
See 1 more Smart Citation
“…The dolphin distribution feature, similar to other cetaceans, mostly results from their foraging for prey (Davis et al 2002;Moura et al 2012;Thorne et al 2012). Studies of the humpback dolphin feeding habits demonstrated that above 20 kinds of demersal and shoaling fish found in productive estuaries were inclusive in their diet (Barros & Cockcroft 1991;Barros et al 2004;Jefferson & Karczmarski 2001;Pan et al 2013;Parra 2006;Parra & Jedensjö 2009;Ross et al 1994;Wang 1965;Wang 1995). That's why the humpback dolphins preferred to estuaries, for feeding on diverse and abundant fish.…”
Section: Habitat Preferencementioning
confidence: 99%
“…The Indo-Pacific humpback dolphin (Sousa chinensis), a small cetacean, has an extensive range in shallow coastal waters from northern Australia and central China to South Africa, including at least 32 countries and territories Jefferson & Karczmarski 2001). Due to inhabiting close to coasts, most stocks are threatened by range-wide incidental mortality in fishing gear, and habitat degradation and loss (Jefferson & Karczmarski 2001;Ross et al 1994). The dolphin population is decreasing, and its status was defined as Near Threatened (NT) (IUCN 2015).…”
Section: Introductionmentioning
confidence: 99%